“We Can Do It” [Wir schaffen das]—Creative Impulses Through Migration (a Report from September 2017, with an Afterword on the Situation Today) (Konturen, 2020)
Geopolitical changes have always caused human beings to leave their domiciles and seek new homelands. The countries that accept them profit both from their capacity to work and their creative potential. In recent decades, Germany too has come to define itself as a land of immigrants, and in the meantime the effects of the arrival of people from Eastern countries, from Turkey, from the former Yugoslavia after it was destroyed by war, and since 2015 in larger numbers from Syria, Afghanistan, and Iraq, are mirrored in German-language literature. This essay attempts to provide a report on recent authors and new literary publications in connection with current political changes in Germany, e.g. the growth of parties and tendencies hostile to foreigners.